A Case Report of Umbilical Vein Varix with Thrombosis: Prenatal Ultrasonographic Diagnosis and Management. (6th August 2019) - Matsumoto, Yuuki; Yanai, Akihiro; Kamei, Saori; Yamaguchi, Ayaka; Nakamine, Hirokazu; Fujita, Kohei
Abstract : Umbilical vein varix (UVV) is a very rare cord anomaly associated with intrauterine fetal death and fetal anomaly. We describe a case of extra-abdominal UVV with thrombosis. UVV was diagnosed at 23 weeks of gestation for the first time by ultrasonographic screening. Peak systolic velocity (PSV) near the UVV was partially increased up to about 100 cm/s, and blood flow was not detected in one of the umbilical arteries at 28 weeks of gestation. Therefore, the mother was hospitalized to monitor alterations of the PSV of the UVV frequently. Because the PSV of the UVV showed a sudden rapid increase up to about 150 cm/s at 32 weeks of gestation, she underwent emergent cesarean section on the same day to avoid sudden umbilical cord occlusion. The infant's birth weight was 1, 744 g, and the Apgar scores were 8 and 9 at 1 and 5 minutes, respectively. The pathological examination showed UVV with thrombosis and an occlusion in one of the umbilical arteries. The neonatal laboratory data showed no coagulopathy. Based on our experience with this case, frequent ultrasonographic examination should be performed to detect the acute thrombosis in the case of extra-abdominal UVV, especially during the preterm period.